2017
DOI: 10.1103/physrevb.96.165425
|View full text |Cite
|
Sign up to set email alerts
|

Microwave analog of Stern-Gerlach effects using nonuniform chiral metamaterials

Abstract: This study observes microwave beam splitting dependent on circular polarizations through nonuniform chiral metamaterials. Nonuniform chiral metamaterials with a gradation in refractive index are constructed using chiral meta-atoms that exhibit optical activities at microwave frequencies. Microwave scattering far-field patterns by the nonuniform chiral metamaterials demonstrate a deflection of microwaves, which transmit in a direction perpendicular to the refractive index gradient. Furthermore, circularly polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…spatial variation in the meta-atom or metamolecule density-in a direction perpendicular to the wave incident direction. The refractive index gradient due to the spatial variation deflects the center of gravity of the beam [29]. If the metamaterials consist of nonreciprocal MCh metamolecules, the bending direction depends on the beam propagation direction.…”
Section: Mo Parameter In Electric Permittivity Tensormentioning
confidence: 99%
See 3 more Smart Citations
“…spatial variation in the meta-atom or metamolecule density-in a direction perpendicular to the wave incident direction. The refractive index gradient due to the spatial variation deflects the center of gravity of the beam [29]. If the metamaterials consist of nonreciprocal MCh metamolecules, the bending direction depends on the beam propagation direction.…”
Section: Mo Parameter In Electric Permittivity Tensormentioning
confidence: 99%
“…In this work, we have demonstrated that a metamolecule can boost MCh effects by several orders of magnitude compared to natural molecules. The enhanced and giant MCh effects thus open a door toward the realization of synthetic gauge fields [22][23][24][25][26][27][28][29]-for example, an effective magnetic field for electromagnetic waves. However, the values of nonreciprocal refractive index differences owing to the MCh effects by the single metamolecule were not yet large.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The present result provides an insight to the understanding of spin-orbit interaction of light. Last but not least, although implemented by microwave meta-atoms, the physical picture unveiled here applies to a broader class of artificial photonic structures in a wide range of frequencies from microwave [51] to visible light [52,53].…”
Section: Origin Of the Asymmetric Field Profiles And Energy Distrimentioning
confidence: 99%